Detoxification vs non-detoxification before starting an anti-CGRP monoclonal antibody in medication overuse headache. (June 2022) - Pensato, Umberto; Baraldi, Carlo; Favoni, Valentina; Mascarella, Davide; Matteo, Eleonora; Andrini, Giorgia; Cainazzo, Maria Michela; Cortelli, Pietro; Pierangeli, Giulia; Guerzoni, Simona; Cevoli, Sabina
Abstract: Background: Medication overuse headache significantly contributes to the chronification process and treatment refractoriness of migraine. Currently, abrupt discontinuation of the overused medication still represents the best management strategy for these patients, challenging public health system resources. Methods: In this prospective study, chronic migraine and medication overuse headache sufferers with at least 28 days of analgesic consumption per month were included. Assessment of efficacy outcomes at three months were compared among patients who underwent in-hospital abrupt discontinuation of overused acute medication (YES-DETOX group) and patients who did not (NO-DETOX group) before starting an anti-CGRP monoclonal antibody. Results: Of 401 patients who received either erenumab or galcanezumab, 28% (n = 111) satisfied inclusion criteria (YES-DETOX n = 28; NO-DETOX n = 83). After three months of treatment, 59% (n = 65; 47/83 YES-DETOX; 18/28 NO-DETOX) patients reverted from medication overuse headache and 51% (n = 57; 42/83 YES-DETOX; 15/28 NO-DEOTX) achieved ≥50% reduction in monthly headache days; yet no statistical differences were observed between the two groups (p = 0.4788 and p = 0.8393, respectively). Monthly consumption of pain medication was the only baseline prognostic factor in multivariate analysis in the overall cohort (p = 0.016). Conclusion: Our results support the emerging evidence that anti-CGRP monoclonal antibodies may be effective in medication overuse headache patients irrespective of detoxification, yet further studies are needed to draw definitive conclusions.